THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN SHAPING STUDENT’S CHARACTER - Shiddiqoh, Ilham (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research explores and analyzes the role of Islamic Religious Education learning in forming student character at the Siti Chodijah Islamic Elementary School, Probolinggo. Islamic religious education is vital in shaping student character, especially at the elementary level in Islamic schools. This research uses a qualitative approach with a case study method to explore students' experiences and perceptions of Islamic Religious Education learning at Siti Chodijah Islamic Elementary School. Data was collected through observation, interviews, and document analysis. The research results show that learning Islamic Religious Education at Siti Chodijah Islamic Elementary School significantly shapes student character. A learning process that integrates Islamic values, ethics, and morality can positively impact students' character development. The Islamic Religious Education teacher at this elementary school plays the leading role as a facilitator of character formation by teaching the values of faith, noble morals, and Islamic social attitudes. Apart from that, a school environment based on Islamic values also shapes student character. Collaboration between schools, teachers, and parents is the key to creating an educational environment supporting character formation. These findings can be a reference for Islamic schools and related parties to continue improving the quality of Islamic Religious Education learning to shape students' character with integrity and competitiveness in society.